Analysis of Total Phenolic Content and Antioxidant Activity of Pakcoy Leaves Using A UV-Vis Spectrophotometer - Della Putri Yuansari Fatmadi; Eva Agustina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Pakcoy (Brassica rapa L.) is a green leafy vegetable known to contain various bioactive compounds, particularly phenolic compounds that act as natural antioxidants. However, quantitative data regarding the total phenolic content and antioxidant activity of pakcoy leaf methanol extract remain limited and show inconsistent results depending on extraction methods and solvents used. Therefore, this study aimed to determine the total phenolic content and antioxidant activity of pakcoy leaf methanol extract using a UV–Vis spectrophotometric approach. The sample used in this study was fresh pakcoy leaves collected from the Gunung Anyar area, Surabaya. Extraction was carried out using the maceration method with 70% methanol as solvent. Total phenolic content was analyzed using the Folin–Ciocalteu method with gallic acid as a standard at a wavelength of 764 nm, while antioxidant activity was evaluated using the DPPH method. Data were analyzed quantitatively using linear regression for calibration curves and IC₅₀ determination. The results showed that the total phenolic content of pakcoy leaf methanol extract was 3.68 mg GAE/g extract. Antioxidant activity analysis resulted in an IC₅₀ value of 13.59 µg/mL, indicating a very strong antioxidant category. The linear regression analysis demonstrated a strong correlation between concentration and absorbance, confirming the reliability of the method used. In conclusion, the methanol extract of pakcoy leaves contains phenolic compounds that significantly contribute to its antioxidant activity. This study provides more specific quantitative evidence supporting the potential of pakcoy leaves as a natural antioxidant source and highlights the importance of solvent selection in optimizing bioactive compound extraction.